A lymphostatin homologue from Chlamydia pecorum inhibits mitogen-activated bovine T cell proliferation and IFNγ production - Elizabeth A. Blackburn; Cosmin Chintoan-Uta; Andrew G. Bease; Maarten W. Tuijtel; Max Hateley; Martin Wear; David Longbottom; Robin Cassady-Cain; Mark P. Stevens (Virulence)
Pathogens frequently produce proteins to evade or inhibit host immune responses. One such protein is lymphostatin from attaching and effacing Escherichia coli (also known as lymphocyte inhibitory factor A; LifA), which influences intestinal colonization and inhibits mitogen- and antigen-activated proliferation of T lymphocytes and pro-inflammatory cytokine synthesis. Here, we report the cloning, purification and characterization of a LifA homologue from Chlamydia pecorum. The predicted 382 KDa protein (CPE2_0552) exhibited 36% identity and 55% similarity over 3171 amino acids to lymphostatin from enteropathogenic E. coli strain E2348/69. CPE2_0552 shares glycosyltransferase and cysteine protease motifs required for lymphostatin activity, including similarity in the tertiary structure of these domains predicted by AlphaFold 3. Purified CPE2_0552 did not share the L-shaped globular structure of lymphostatin when analyzed by transmission electron microscopy. CPE2_0552 inhibited concanavalin A-stimulated proliferation of bovine T cells in a concentration-dependent manner, with an inhibitory dose 50 (ID50) of 812 pg/mL. This was 38-fold higher than the ID50 of E. coli E2348/69 lymphostatin tested in parallel on T cells from the same donors (21 pg/mL), but was similar to another LifA homologue from E. coli O157:H7 (ToxB). Moreover, CPE2_0552 inhibited the secretion of interferon gamma (IFNγ), a key cytokine that influences the outcome of Chlamydia infections. At the concentrations at which CPE2_0552 inhibited T lymphocyte proliferation and IFNγ secretion, negligible cytotoxicity was observed after 72 h of stimulation. Our study indicates that E. coli lymphostatin belongs to a wider family of lymphocyte-inhibitory molecules that exist in distantly related bacterial pathogens.